Concentrations of neopterin, kynurenine and tryptophan in wound secretions of patients with breast cancer and malignant melanoma: a pilot study - Mergancova, Jana; Javorska, Lenka; Šiller, Jiří; Sákra, Lukáš; Mergancova, Jindriska; Solichova, Dagmar; Krcmova, Lenka Kujovska; Melichar, Bohuslav; Mohelnikova-Duchonova, Beatrice; Studentova, Hana; Klos, Dusan (Walter de Gruyter GmbH & Co. KG, 2017)
The aim of the present pilot study was to investigate the concentrations of neopterin, kynurenine and tryptophan in wound secretion in patients undergoing surgery for breast cancer or malignant melanoma. Twenty-two patients, 16 females and 6 males, undergoing surgery for breast cancer (n = 15) or malignant melanoma (n = 7) were evaluated. Neopterin, kynurenine and tryptophan were determined using a high-performance liquid chromatography method. When the concentrations in wound secretions from the primary breast tumor and the axilla were compared, the neopterin/tryptophan ratio was significantly higher in the tumor wound secretions (0.92 +/- 0.41 vs. 0.61 +/- 0.14 mmol/mol; p = 0.049), but no significant differences were observed in neopterin (49.2 +/- 28.6 vs. 31.5 +/- 11.1 nmol/L), tryptophan (52.9 +/- 13.0 vs. 51.2 +/- 13.3 mu mol/L) and kynurenine concentrations 5.97 +/- 7.49 vs. 5.34 +/- 6.25 mu mol/L) and kynurenine/tryptophan ratio (108.1 +/- 107.7 vs. 103.5 +/- 106.7 mmol/mol). No marked differences were noted in neopterin, tryptophan and kynurenine concentrations and kynurenine/tryptophan and neopterin/tryptophan ratios in sequential samples from the axilla of breast cancer patients obtained on days 1 and 2. In conclusion, present data demonstrate that the measurement of neopterin, kynurenine and tryptophan can be used to monitor local immune response after cancer surgery.
Koncentrace neopterinu, kynureninu a tryptofanu v sekretu z rány u pacientů s karcinomem prsu a maligním melanomem: pilotní studie
Keywords: breast cancer; kynurenine; melanoma; neopterin; tryptophan; karcinom prsu; kynurenin; melanom; neopterin; tryptofan.